APAKAH LOKASI MENENTUKAN KESUKSESAN BISNIS? KASUS BISNIS APOTEK DI YOGYAKARTA DAN SURAKARTA - Indarti, Nurul; Wahyudi, Erlisetya; Chandra, Ramelan (Journal of Indonesian Economy and Business, 2005)
This study aims to identify location factors of pharmacy business and their associationwith business success. Respondents of survey are 82 pharmacy businesses in Yogyakartaand Surakarta. Regression analysis reveals that there are five location factors that havesignificant relationship with business success. These factors are proximity to main road,proximity to hospital/clinics, availability of business venue, proximity to housing, and beingin business centre. Altogether these factors explain 49.8% of total variance. In addition tofavourable location, other factors are also identified to be important in the pharmacybusinesses. These factors include complete assortment of medicines, affordable prices,relationship with doctors, and customer service related factors.Keywords: location factor, business success, pharmacy business.